Characterization of fish farming practices and performance: Baseline study and implications for accelerating aquaculture development in Ghana - Ragasa, Catherine; Agyakwah, Seth K.; Asmah, Ruby; Mensah, Emmanuel Tetteh-Doku; Amewu, Sena (International Food Policy Research Institute, 2020)
Over the past decade, the aquaculture sector in Ghana has experienced tremendous growth—driven mainly by large-scale cage farms—but it has been unclear how the rural poor have shared in this growth. A research project has been initiated to help diagnose, design, and test interventions for better inclusion of the rural poor, women, and youth in the tilapia value chain. This report describes the baseline data on 603 small-scale tilapia farmers in Ghana. The data collected during two-hour face-to-face interviews during May–July 2019 are disaggregated by socioeconomic indicators, gender, and age group. Baseline data show that 9 percent of farm managers and owners were women, and an additional 9 percent of farms engaged women in some decision-making. Moreover, women contributed 16 percent of family labor and 5 percent of hired labor on farms. Youth represented 14 and 24 percent of owners and managers, respectively, but contributed 68 percent of the total family and hired labor on farms. A large majority of managers and owners had at least high school education, with a third of owners and a quarter of managers attaining at least a college degree. In Brong Ahafo and Ashanti regions especially, most farmers engaged mainly in crop farming and non-farm businesses as their main livelihood, with fish farming as a small contributor to overall household income and livelihood. Farmers in all regions had poor record-keeping and management practices and low compliance with sanitation, fish health, and food safety standards. A wide variety of input usage, management practices, and performance was observed among fish farms. As a result, the profitability of fish farms was also wide-ranging, between –12.00 and 46.00 cedi per m2, with an average of 8.82 cedi per m2. Despite wide variability in production and profits, the majority of farmers experienced positive profits. On average, a farmer received a profit of 2.4 cedi per kilogram of tilapia produced or a 27 percent profit margin. These encouraging figures indicate that farmers who adopt good aquaculture practices can achieve respectable profits.